Treatment Tactics for Locally Distributed Tumour Lesions of the Bladder with the Involvement of the Anterior Abdominal Wall: a Clinical Case - V. N. Pavlov; N. V. Kalakutsky; V. N. Vavilov; M. F. Urmantsev (Креативная хирургия и онкология, 2020)
Introduction. At the present stage of the development of oncological surgery, pelvic evisceration (PE) has ceased to be used as a palliative method and has established itself as an effective method of surgical treatment for locally distributed pelvic tumours. This type of intervention using the methods of the reconstructive plastic restoration of postoperative defects allows the number of postoperative complications to be reduced and the patients’ quality of life to be improved.Materials and methods. A 49-year-old man with a progressive locally distributed bladder cancer involving the anterior abdominal wall underwent an anterior PE with the formation of a Bricker ileal conduit, an extensive resection of the anterior abdominal wall with the reconstructive repair of the defect by a thoracodorsal skin-muscular-fascial transplant.Results and discussion. The operation lasted for 435 minutes, of which the reconstructive stage of the operation lasted for 320 minutes. The estimated blood loss was 700 ml. The patient remained in the intensive care unit for 2 days and was discharged on the 11th day after the operation.Conclusion. In the described clinical case, the performed pelvic evisceration with the simultaneous reconstruction of the anterior abdominal wall allowed radical oncological results to be achieved as evidenced by the absence of disease recurrences.